Australian population trends and disparities in cholinesterase inhibitor use, 2003 to 2010. Issue 3 (12th July 2013) - Zilkens, Renate R.; Duke, Janine; Horner, Barbara; Semmens, James B.; Bruce, David G.
Abstract: Background: The Australian Pharmaceutical Benefits Scheme (PBS) first subsidized cholinesterase inhibitors (CEIs) for Alzheimer's disease in 2001, introducing a novel therapy for a previously untreatable common condition. This study aims to determine Australian rates of CEI use and to assess equality of access to treatment based on socioeconomic status and geographic remoteness. Methods: Pharmaceutical claims records were used to identify all Australians prescribed CEIs between January 2003 and December 2010. Age‐standardized and sex‐adjusted index prescription rates were derived using the total Australian population as the denominator to examine temporal trends and the impacts of socioeconomic and geographic disadvantage on CEI index prescription rates. Results: Index prescription rates peaked in 2004 at 92.5 per 100, 000 person‐years, declining to between 70.2 and 73.5 for years 2006 to 2010. Rates were highest in the 85‐ to 89‐year age group and 2.6‐fold higher in the least socioeconomic disadvantaged population when compared with the most disadvantaged population. In major cities in Australia, index prescription rates were 1.4 to 1.7 times greater compared with remote areas. Conclusions: Increasing geographic remoteness and socioeconomic disadvantage are associated with lower CEI index prescription rates, indicating inequities in the management of Alzheimer's disease in Australia.